Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Belanja Modal dengan Sisa Lebih Pembiayaan Anggaran sebagai Pemoderasi: Studi Kasus pada Kabupaten dan Kota di Provinsi Banten Periode 2020-2024 - Raden Doli Tejabaskara; Sigit Budi Santoso; Imam Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on Capital Expenditure, with Budget Surplus (SiLPA) as a moderating variable in district and city governments across Banten Province for the 2020–2024 period. The background of this research is driven by the high regional dependence on central government transfer funds and the suboptimal allocation of capital expenditure as a key indicator of regional development. This study employs a quantitative approach using secondary data from Local Government Budget Realization Reports (LRA), analyzed through Multiple Linear Regression and Moderated Regression Analysis (MRA) using statistical software. The results demonstrate that PAD has a significant positive effect on capital expenditure, whereas DAU and DAK do not show any significant influence. Furthermore, the interaction test reveals that SiLPA is unable to moderate the relationship between PAD, DAU, or DAK and capital expenditure. These findings indicate that regional fiscal independence, through the optimization of PAD, serves as the primary determinant for capital investment. The implications of this study suggest that local governments should further optimize local revenue potential to reduce dependency on transfer funds and improve budget management efficiency to support sustainable regional development.